Increased Risk of Infection with Severe Fever with Thrombocytopenia Virus among Animal Populations on Tsushima Island, Japan, Including an Endangered Species, Tsushima Leopard Cats - Matsuu, Aya; Doi, Kandai; Ishijima, Keita; Tatemoto, Kango; Koshida, Yushi; Yoshida, Ayako; Kiname, Kohei; Iwashita, Akio; Hayama, Shin-ichi; Maeda, Ken (Viruses, 2022)
To investigate the seroprevalence of severe fever with thrombocytopenia syndrome (SFTS) among wild and companion animals on Tsushima Island, Japan, SFTS virus (SFTSV)-specific ELISA and virus-neutralizing tests were conducted on 50 wild boars, 71 Sika deer, 84 dogs, 323 domestic cats, and 6 Tsushima leopard cats. In total, 1 wild boar (1.8%), 2 dogs (2.4%), 7 domestic cats (2.2%), and 1 Tsushima leopard cat (16.7%) were positive for anti-SFTSV antibodies. Among the 11 positive animals, 10 were collected after 2019, and all were found on the southern part of the island. SFTSV, thus far, seems to be circulating within a limited area of Tsushima Island. To protect humans and animals, including endangered Tsushima leopard cats, from SFTSV infection, countermeasures are needed to prevent the spread of SFTSV on Tsushima Island.